Efficient perovskite solar cells for monolithic perovskite-organic tandem solar cells - Xiao, Y (2023)
Climate change and energy crisis are regarded as the two main global challenges threating the modern society. In this context, the development of photovoltaic solar cells has been placed on great expectations due to their clean and renewable energy features. As one representative among the emerging photovoltaic technologies, perovskite solar cells (PSCs) have made huge progress during the past decade. Pairing with another skyrocketing organic solar cells (OSCs), it is expected to further advance the device performance via realizing the monolithic perovskite-organic tandem solar cells (POTSCs), which will be presented in this thesis.